Transanal endoscopic cooperative surgery as a less invasive resection technique for anorectal tumors extending beyond the dentate line: Case series - Kohei Shigeta; Kazunori Takada; Kinichi Hotta; Kenichiro Imai; Sayo Ito; Junya Sato; Yoichi Yamamoto; Masao Yoshida; Yuki Maeda; Noboru Kawata; Hirotoshi Ishiwatari; Hiroyuki Matsubayashi; et al. (Endoscopy International Open)
Endoscopic submucosal dissection (ESD) and surgical local excision pose particular challenges for anorectal tumors extending beyond the dentate line, making technique selection difficult. We hypothesized that combining ESD and local excision (transanal endoscopy cooperative surgery; TaECS) can effectively resect such tumors. TaECS was performed for three patients with anorectal tumors extending beyond the dentate line between January and December 2022. TaECS was indicated for local resection of tumors extending beyond the dentate line with a low risk of lymph node metastases. TaECS was performed in an operating room after ensuring adequate bowel preparation. The oral side of the tumor was dissected endoscopically with resection margins precisely evaluated using magnifying endoscopy. The anal side was surgically dissected above the internal anal sphincter. The defect was repaired wtih bilateral V-Y advancement flap reconstruction. All three tumors were successfully resected in en bloc fashion without intraprocedural adverse events. No postoperative stricture and bleeding occurred. A postoperative abscess around the anastomosis was observed in one case. The anal sphincter was preserved in all cases. No recurrences were recorded at the 17- to 27-month follow-up. TaECS may be a viable treatment for minimally invasive local resection of anorectal tumors extending beyond the dentate line.